2022
DOI: 10.1111/fwb.14001
|View full text |Cite
|
Sign up to set email alerts
|

Fish community composition in small lakes: The impact of lake genesis and fisheries management

Abstract: 1. Gravel pit lakes are common across Europe. These novel ecosystems serve as model systems to study human-induced and natural colonisation of isolated lakes by fish. Fisheries-management activities can quickly spread species over large distances, possibly homogenising fish communities across ecosystems, while fostering local fish diversity.2. Our objective was to evaluate the effects of lake genesis (gravel pit lakes < 100 years old vs. natural lakes of glacial genesis ~10,000 years old) and fisheries managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 151 publications
1
9
0
1
Order By: Relevance
“…However, our study shows that game species such as carp and goldfish are nevertheless frequent in the new lakes, probably as a consequence of illegal release of these species for recreational fishing. These different patterns call for larger scale studies, beyond a single country or region, of fish species richness and the role of management (Matern et al, 2022). The carp is often released by humans due to its recreational value as a game fish (Arlinghaus & Mehner, 2003; Vilizzi, 2012) and has also been observed in Danish gravel pit lakes (Søndergaard et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, our study shows that game species such as carp and goldfish are nevertheless frequent in the new lakes, probably as a consequence of illegal release of these species for recreational fishing. These different patterns call for larger scale studies, beyond a single country or region, of fish species richness and the role of management (Matern et al, 2022). The carp is often released by humans due to its recreational value as a game fish (Arlinghaus & Mehner, 2003; Vilizzi, 2012) and has also been observed in Danish gravel pit lakes (Søndergaard et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recreational fishing is known to influence non-native fish species richness patterns in Europe (Zhao et al, 2016) and North America (Davis & Darling, 2017), where several catchments experienced an increase of almost 50% in richness due to the transferring of game fish to areas where the species were not found previously (Peoples et al, 2020). Studies in Europe have found different patterns in lakes managed for recreational fishing, showing that fish communities are subject to homogenisation (Matern et al, 2019(Matern et al, , 2022 with cases of both elevated (Zhao et al, 2016) and unchanged non-native richness (Matern et al, 2019). While many of the investigated lakes are used for recreational fishing, they are not managed for this purpose, in a way similar to fisheries in other countries (Arlinghaus et al, 2021).…”
Section: Fish Diversity In New Lakesmentioning
confidence: 99%
See 2 more Smart Citations
“…In some gravel pit lake systems, fisheries management interventions such as stocking speed up colonization and promote species‐rich communities that resemble those in natural lakes (Matern et al 2022). We expected that the initial fish community would primarily include stocked fishes; however, these species had a surprisingly small presence in the lake communities despite yearly stocking from 2006 to 2019.…”
Section: Discussionmentioning
confidence: 99%